The Relationship Between Driving Duration And Seating Position And Complaints Of Lower Back Pain Among Minibus Drivers At The Beriman Wilken Terminal In Tomohon - Angel Sharon Margaretha Sinulingga; Theo Mautang; Richard A Palilingan; Lucyana Pongoh; Jonesius E Manoppo; Jilly Toar (CV. AFDIFAL MAJU BERKAH, 2026)
Lower back pain is commonly experienced by minibus public transportation drivers, which is believed to be influenced by the duration of driving and non-ergonomic seating positions. This study aims to determine the relationship between driving duration and sitting position and complaints of lower back pain among minibus public transport drivers at the Beriman Wilken Terminal in Tomohon. A cross-sectional observational study was conducted on 41 drivers. Data were collected via a questionnaire and an assessment of sitting posture using the RULA method. Chi-square test results indicated a significant association between driving duration and lower back pain complaints (p = 0.004) as well as between sitting posture and lower back pain complaints (p < 0.000). The majority of drivers drove more than 8 hours per day and had non-ergonomic sitting positions, which contributed to lower back pain complaints.